Design a sitting shower therapy with water temperature and pressure controller - Eko Arianto (JHeS (Journal of Health Studies), 2022)
The pressure and temperature of the water used when bathing using a shower has been presented to provide physiological changes to the body. However, the ideal water pressure and temperature for shower therapy has not been extensively discussed. Therefore, this research was conducted to design a shower therapy that meets the ideal specifications to obtain the most optimal therapeutic effect. Water pressure regulation was performed with a booster pump controlled by a dimmer circuit. Meanwhile, a linear motor was applied to drive the showerhead, which was controlled by Arduino. The results of the prototype test show that a series of shower therapy can be employed in both sitting and standing positions. The water temperature of 40-60 °C was achieved in 30 minutes of the heating process which indicates that the developed tool needs improvement in future research, to attain a shorter heating time and a more accurate shower head movement speed.